2002
DOI: 10.1016/s0022-3093(01)01015-8
|View full text |Cite
|
Sign up to set email alerts
|

Electronic transport in low temperature nanocrystalline silicon thin-film transistors obtained by hot-wire CVD

Abstract: Hydrogenated nanocrystalline silicon obtained by Hot-Wire Chemical VapourDeposition has been incorporated as the active layer in bottom-gate thin-film transistors.These devices were electrically characterised by measuring in vacuum the output and transfer characteristics for different temperatures. The field-effect mobility showed a thermally activated behaviour which could be attributed to potential barriers for the electronic transport. Trapped charge at the interfaces of the columns, which are typical in hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
2
1
0
Order By: Relevance
“…4 shows the dependence of barrier height E b , near the Ac-Si:H grain-GB region of columnar grains, with sizes L, varying from 100 to 200 nm. For a nc-Si:H TFTs it has been found that the density of charged states at the column boundaries is around 3.0 Â 10 11 cm À 2 for the column width of 100 nm and barrier height 70-80 meV with volume charge density N v¨1 0 17 cm À 3 [18]. This result is in good agreement with our AMPS-1D simulation results (Fig.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…4 shows the dependence of barrier height E b , near the Ac-Si:H grain-GB region of columnar grains, with sizes L, varying from 100 to 200 nm. For a nc-Si:H TFTs it has been found that the density of charged states at the column boundaries is around 3.0 Â 10 11 cm À 2 for the column width of 100 nm and barrier height 70-80 meV with volume charge density N v¨1 0 17 cm À 3 [18]. This result is in good agreement with our AMPS-1D simulation results (Fig.…”
Section: Resultssupporting
confidence: 90%
“…This n t value agrees with the density of charged states at the column boundaries estimated by the Levinson technique [18].…”
Section: Resultssupporting
confidence: 86%
“…However, to date, only top gate (TG) TFTs have been produced with field effect mobilities greater than a-Si:H devices. Bottom gate (BG) TFTs, on the other hand, tend to yield devices with field effect mobilities that are below 1 cm 2 V À1 s À1 [5,6].…”
Section: Introductionmentioning
confidence: 99%